Innovative work behavior and turnover intention: A conceptual model - Hendryadi Hendryadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This article develops a conceptual framework to examine the dual effect of Innovative Work Behavior (IWB) on Turnover Intention (TI), recognizing that innovation can both reduce and increase employees' desire to leave an organization depending on contextual conditions. Drawing on multiple theoretical perspectives—including Social Exchange Theory, the Job Demands-Resources (JD-R) Model, Self-Determination Theory, Leader-Member Exchange (LMX) Theory, Affective Events Theory, and Organizational Justice Theory—the proposed framework identifies key mediating mechanisms (LMX, work engagement, organizational commitment, and job satisfaction) that explain how IWB influences turnover intention, as well as critical moderating factors (perceived organizational support, distributive fairness, and organizational culture) that shape the strength and direction of this relationship. The framework acknowledges that while IWB can enhance employee retention when supported and recognized, it may also increase turnover intention in contexts characterized by hierarchical cultures, low support, or unfair reward systems. By integrating both the bright and dark sides of innovation, this conceptual paper contributes to a more nuanced understanding of the relationship between IWB turnover intention. It provides a foundation for future empirical testing. The framework offers practical implications for public service organizations and other contexts seeking to balance innovation promotion with employee satisfaction and stability.